Elevated levels of cerebrospinal fluid α-synuclein oligomers in healthy asymptomatic LRRK2 mutation carriers - Aasly, Jan O.; Johansen, Krisztina K.; Brønstad, Gunnar; Warø, Bjørg J.; Majbour, Nour K.; Varghese, Shiji; Alzahmi, Fatimah; Paleologou, Katerina E.; Amer, Dena A. M.; Al-Hayani, Abdulmonem; El-Agnaf, Omar M. A. (Frontiers in Aging Neuroscience, 2014)
Mutations in the leucine-rich repeat kinase 2 gene are the most common cause of autosomal dominant Parkinson’s disease. To assess the cerebrospinal fluid levels of α-synuclein oligomers in symptomatic and asymptomatic leucine-rich repeat kinase 2 mutation carriers. We used enzyme-linked immunosorbent assays to investigate total and oligomeric forms of α-synuclein in cerebrospinal fluid samples. The cerebrospinal fluid samples were collected from 33 Norwegian individuals with leucine-rich repeat kinase 2 mutations: 13 patients were clinically diagnosed with Parkinson’s disease and 20 patients were healthy, asymptomatic leucine-rich repeat kinase 2 mutation carriers. We also included 35 patients with sporadic Parkinson’s disease and 42 age-matched healthy controls. Levels of cerebrospinal fluid α-synuclein oligomers were significantly elevated in healthy asymptomatic individuals carrying leucine-rich repeat kinase 2 mutations (n = 20; P < 0.0079) and in sporadic Parkinson’s disease group (n = 35; P < 0.003) relative to healthy controls. Increased α-synuclein oligomers in asymptomatic leucine-rich repeat kinase 2 mutation carriers showed a sensitivity of 63.0% and a specificity of 74.0%, with an area under the curve of 0.66, and a sensitivity of 65.0% and a specificity of 83.0%, with an area under the curve of 0.74 for sporadic Parkinson’s disease cases. An inverse correlation between cerebrospinal fluid levels of α- synuclein oligomers and disease severity and duration was observed. Our study demonstrated that quantification of α-synuclein oligomers in cerebrospinal fluid has potential value as a tool for Parkinson’s disease diagnosis and presymptomatic screening of high-risk individuals.